Selección de morfotipos de hongos Micorrízicos arbusculares nativos predominantes de suelos degradados asociados a plantas de cobertura de la sub cuenca del Cumbaza - Barrios López, Lleny (2017)
In order to select and identify the different morphotypes of predominant native arbuscular mycorrhizal fungi (AMH) and determine the percentage of colonization and spore density in soils of the Cumbaza subbasin associated to cover plants, degraded soils were selected from the localities of Chirikyacu, Vista Alegre, El Chontal, San Antonio, Aucaloma, and Shapumba; where soil samples were collected and associated with four legumes covering Cajanus cajan, Canavalia ensiformis, Crotalaria juncea and Vigna unguiculata. A completely randomized design with factorial arrangement of 6Ax4B was used, with three replications and at significance level of p <0.05, considering factor A (zone) and factor B (legume). The results showed that the legumes had a greater influence on the percentage of mycorrhizal colonization compared to the areas under study, with Vigna unguiculata having the highest percentage of colonization with 75%. The highest number of spores was influenced mainly by the zones, where Aucaloma presented the largest number with 332 spores / 10 g. Finally, 11 predominant native HMA morphotypes were identified, with the morphotypes of the genus Acaulospora being the most predominant.